Kant and Degrees of Responsibility. Issue 1 (4th January 2018) - Saunders, Joe
Abstract: Kant views every human action as either entirely determined by natural necessity or entirely free. In viewing human action this way, it is unclear how he can account for degrees of responsibility. In this article, I consider three recent attempts to accommodate degrees of responsibility within Kant's framework, but argue that none of them are satisfying. In the end, I claim that transcendental idealism constrains Kant such that he cannot provide an adequate account of degrees of responsibility.